Menumbuhkan Gaya Hidup Sehat Sejak Dini Melalui Pendidikan Jasmani, Olahraga, Dan Kesehatan - Agus Mulyana; Dela Lestari; Dhilla Pratiwi; Nabila Mufidah Rohmah; Nabila Tri; Neng Nisa Audina Agustina; Salma Hefty (Pusat Riset dan Inovasi Nasional, 2024)
A healthy lifestyle is a basic human need that is important to be nurtured from an early age through physical education, sports and health (PJOK). This study aims to explore effective methods to instill healthy habits in primary school students. Using a qualitative approach, this study reviewed literature from various sources to identify the best strategies for teaching healthy lifestyles. The results showed that storytelling, FGDs, ice-breaking, and the use of appropriate learning media are very effective in increasing students' understanding and motivation about the importance of a healthy lifestyle. In addition, physical education plays an important role in shaping students' understanding and behavior towards a healthy lifestyle through a curriculum that is integrated with physical activity. Families and communities also play an important role in supporting these efforts by providing a supportive environment and good role models. The main challenges in instilling healthy habits are resistance to change and the influence of unhealthy habits from the environment. Proposed solutions include consistency in setting good examples, variety of healthy foods, and cooperation between educators and parents.